Evaluation of confirmatory data following the Article 12 MRL review and setting of import tolerances for bifenthrin in maize grain and sweet corn. (23rd December 2020) - ; Anastassiadou, Maria; Bernasconi, Giovanni; Brancato, Alba; Carrasco Cabrera, Luis; Ferreira, Lucien; Greco, Luna; Jarrah, Samira; Kazocina, Aija; Leuschner, Renata; Magrans, Jose Oriol; Miron, Ileana; et al.
Abstract: The applicant FMC Agricultural Solutions A/S submitted a request to the competent national authority in Belgium to evaluate the confirmatory data that were identified in the framework of the maximum residue level (MRL) review under Article 12 of Regulation (EC) No 396/2005 as not available. To address the data gaps, a new storage stability study was submitted and information on an analytical method for determination of bifenthrin in eggs was made available. The data gaps were sufficiently addressed. The new information provided, did not require a revision of the existing MRLs. In addition, in accordance with Article 6 of Regulation (EC) No 396/2005, the applicant submitted a request to set import tolerances for bifenthrin in sweet corn and maize grain. The data submitted in support of the request were found to be sufficient to derive an MRL proposal for maize grain only. For sweet corn, data gaps were identified which precluded the derivation of an MRL proposal. Adequate analytical methods for enforcement are available to control the residues of bifenthrin (sum of isomers) in plant matrices under consideration at the validated limit of quantification (LOQ) of 0.01 mg/kg and in animal matrices. EFSA concluded that the short‐term and long‐term intake of residues resulting from the uses of bifenthrin according to the reported agricultural practices is unlikely to present a risk to consumer health. The risk assessment is affected by additional non‐standard uncertainty related to the expiry of EU authorisation for a number of crops for which previously EU MRLs were established, and which are still included in the risk assessment.